Menilai Efektivitas Fogging Fokus Menggunakan ThermalFog Dan UltraLow Volume (ULV) dengan Insektisida Malathion dalam Pengendalian Vektor Demam Berdarah (Studi Di Wilayah Kerja Puskesmas Tlogosari Wetan Kota Semarang) - Zefira Sausan Archiarafa; Ludfi Santoso; Martini Martini (Jurnal Kesehatan Masyarakat (Undip), 2016)
All this time fumigation has been often used as the principal method of controlling DHF in some countries over half of this decade, but the results are not so satisfy, as shown by an increase in the incidence of dengue in the same time. This study aimed to evaluate focus Fogging  usingThermalFog and ULVportable in dengue vector control. The method used is a quasi-experimental design with non-randomized control group pretest posttest design. Samples in this study are 25 houses in each application area of the whole house is in the application area. Analysis of data using different test Wilcoxon and Mc-Nemar. The results showed that there was no difference in HI, OI and the number of eggs between before Fogging with after  1st Fogging and after 1st Fogging with after 2nd Fogging  on both application (p value> 0.05). On the application of ULVportable, p value before-after Fogging 1: HI = 0.063, OI = 0.774, and the amount of eggs = 0.649 while the p value after Fogging 1-after Fogging 2: HI = 1.000, OI = 0.289, and the amount of eggs = 0.358 , Then in ThermalFog, p value before-after Fogging 1: HI = 0.625, OI = 0.267, and the amount of eggs = 0.255 while the p value after Fogging 1-after Fogging 2: HI = 0.500, OI = 0.344, and the amount of eggs = 0.683.The author suggested the city health office to further tighten supervision and evaluation of Fogging and to the public that rely more eradication of mosquito breeding plasce than Fogging.